1987
DOI: 10.1111/j.1699-0463.1987.tb00037_95a.x
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOHISTOCHEMICAL CHARACTERIZATION OF INTRAEPIDERMAL IN VIVO IgG DEPOSITS IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME

Abstract: Immunohistochemical characterization of intraepidermal in vivo IgG deposits in patients with primary Sjogren's syndrome. Acta path. microbiol. immunol. scand. Sect. A. 95: 239-244, 1987. 68% of patients with primary Sjogren's syndrome have previously been found to have intra-epidermal in vivo IgG deposits in clinically unaffected skin. In this investigation, we examined immunohistologically skin biopsies from 5 patients with primary Sjogren's syndrome and from 5 normal controls in order to characterize furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The ocular surface of a dry eye with its persistent dry spots, epithelial ulcers, excessive mucin plaques and corneal filaments is the result of both local epithelial disease and regional glandular dysfunction. In 1"SS it is the result of a generalized exocrinopathy (Frost-Larsen et al 1980) which also involves the tear glands resulting in KCS, but the disease seems to involve all epithelia (Oxholm et al 1987) including the epithelia of the ocular surface (Prause et al 1989). Despite the systemic nature of the disease, only few systemic drugs have proven to have an effect Prause et al 1984;Oxholm et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The ocular surface of a dry eye with its persistent dry spots, epithelial ulcers, excessive mucin plaques and corneal filaments is the result of both local epithelial disease and regional glandular dysfunction. In 1"SS it is the result of a generalized exocrinopathy (Frost-Larsen et al 1980) which also involves the tear glands resulting in KCS, but the disease seems to involve all epithelia (Oxholm et al 1987) including the epithelia of the ocular surface (Prause et al 1989). Despite the systemic nature of the disease, only few systemic drugs have proven to have an effect Prause et al 1984;Oxholm et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that subclasses IgGl and IgG3 only are deposited, in graft epidermis as well as in patient skin (9), is of interest in view of the fact that Fc-receptors on mononuclear cells bind only these subclasses (10). Epidermal Fc-receptors are predominantly found on LC, but keratinocytes have also been shown to exhibit these IgG-binding receptors (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have shown that IgG is predominantly attached to the surface of Langerhans cells (LC) (9), that only IgGl and IgG3 are deposited (7,9) and that such deposits seems to be of diag-nostic significance (8). We have suggested that IgG-containing immune complexes (IC) may be involved in the epidermal IgG deposits (8).…”
mentioning
confidence: 99%